Sifat Fisika dan Mekanika Papan Partikel Berbahan Limbah Industri PT. Aldi Mandomai Mebel: Physical and Mechanical Properties of Particle Boards Are based on Industries Waste of PT. Aldi Mandomai Furniture - Mahdi Santoso; Desy Natalia Koroh; Prona Rogaya Rambe; Grace Siska; Yanarita Yanarita (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
This research aims to determine the effect of particle sizes (10 mesh, 20 mesh, and 30 mesh) on the physical and mechanical properties of particleboards made from industry waste of PT. Aldi Mandomai Furniture, based on JIS A 5903: 2003 Standard. . Particleboards size were 30 x30x1,5 cm, density 0,5 g/cm3. Moisture content particles at 5%, particles glued with urea-formaldehyde adhesives, weight 10%, hot press pressured with temperature 110 ± 20C for 15 minutes, pressure 25 kg/ cm2. Furthermore, particleboards must be conditioned for ± 14 days/ 2 weeks. Particleboards were cut into sample test according to the size in the JIS A 5903:2003 standard. Research design used Completely Random Design with one factor. Data analyzed using analysis of variance, if data was significant must to do areal difference test. The observed to particle size with 3 levels are 10 mesh, 20 mesh, and 30 mesh. The results of physical properties were Density ( a.v. 0,46 – 0,49 g/cm³), Moisture Content (a.v. 12,22 – 14,05%), Water Absorption (a.v 129,79 – 167,03%), and Thickness Swelling (a.v 11,43 – 22,08%). The results of mechanical properties were internal bonding (0,0075 - 0,0204 N/mm2), Modulus of Elasticity (a.v. 5,91 – 25,32 N/mm2), Modulus of Rupture (a.v 0,52 – 1,52 N/mm2 ), and Screw Holding (a.v. 29,42 – 104,60 N). Particleboards made from furniture industry waste with particle size 10 mesh was significantly to physical properties, except density and fulfill JIS A 5903:2003, while the mechanical properties of particleboard are not fulfill the standard.